The feminist classroom: women's action in the reinvention of adult learning spaces - Shubane, Letlhabile Monica (My University, 2017)
My focus is on working women in post democracy education and training programmes. Due to societal gender roles, rights for women, in both education and opportunity, should materialise in adult education systems. In order for women to be exposed to work opportunities as well as to maintain the domestic and child-rearing roles they play in society, these systems and spaces must be reinvented. I hope to defi ne indigenous feminist theories, and then to manifest these in the creation of learning spaces. Th rough deconstructing the hugely diverse lived experiences of women in their social roles, I will question educational subject matter, women’s representation as learners, workplace roles, domestic and child-rearing roles, and fi nally challenge the idea of the widely accepted school and classroom model as a centralised institution. Alternative practices of learning and knowing possibly have great impact on transformation for women. Th e ties between education and work lead me to choose factories as my site of interest. Th e site of Jeppestown is appropriate because it is where the light industrial practices about which I am talking, continue to exist. With this thesis I aim to propose an alternative model for working- women as students and educators. I aim to reinvent the systems and spaces in which women learn and in which contextualised feminist theories are manifested.
Thesis is submitted in partial fulfilment for the degree of Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, School of Architecture and Planning at the University of the Witwatersrand, Johannesburg, 2017
Keywords: City planning--South Africa; Architectural design--Study and teaching--South Africa; Feminism and education--South Africa; Adult education--South Africa; Literacy programs--South Africa